Attitudes of Students From a Public University About the Application of the Flipped Learning - Chambi-Mescco, Edith (2021)
The approach called flipped learning has been attracting teachers’ attention in recent years due to its novel way of programming and executing learning sessions, thus making a difference with the traditional model. This approach has been applied in various higher education programs; the results express the achievements that have been obtained in terms of learning thanks to its implementation. The purpose of the present research article is to identify students’ attitudes from the second cycle of General Studies of a Peruvian public university after having experienced the flipped learning in the course Language and Communication in the academic semester 2018-II. This study is quasi-experimental and of a mixed approach. A questionnaire prepared by Farrah y Qawasmeh (2018) was applied to collect the attitudes of 70 students grouped into two classrooms and developed the subject directed by the same teacher. The results show that most students consider that the pedagogical approach called flipped learning is highly beneficial for their learning because it promotes developing the necessary skills for their professional training. The results also suggest that its effectiveness depends on the students’ autonomy to develop the previous activities and the easy access they could have to the Internet.